2019
DOI: 10.7150/jbji.37262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Antibiotic Suppressive Therapy in Patients with a Prosthetic Joint Infection after Hip Replacement

Abstract: Abstract. Introduction: In Specific cases, curative treatment of a prosthetic joint infection (PJI) cannot be accomplished due to the increased risk of major complications after prosthetic joint revision surgery. In these patients, antibiotic suppressive therapy (AST) is often used to control the infection.Aim: To describe the clinical outcome of patients with a PJI after hip replacement treated with AST.Methods: Patients in which AST for PJI was started between 2006 and 2013, were retrospectively included. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
3
20
2
Order By: Relevance
“…Linezolid offers the advantage of very good, oral bioavailability (Thompson et al, 2017) and its broad spectrum against Gram-positive bacteria facing current resistance patterns (Deroche et al, 2019;Lourtet-Hascoet et al, 2018) of organisms encountered in the treatment of PJI. Based on the reports available and included in this review a remission of the infection can be expected in around 80 % of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linezolid offers the advantage of very good, oral bioavailability (Thompson et al, 2017) and its broad spectrum against Gram-positive bacteria facing current resistance patterns (Deroche et al, 2019;Lourtet-Hascoet et al, 2018) of organisms encountered in the treatment of PJI. Based on the reports available and included in this review a remission of the infection can be expected in around 80 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal antibiotic treatment length in PJI is currently unknown (Aboltins et al, 2019). However, long-term or life-long treatment algorithms were recommended by some guidelines and authors (Leijtens et al, 2019;Osmon et al, 2013b;Calabro et al, 2019;Aboltins et al, 2019), and duration of treatment might play a vital role (Tattevin et al, 2006) -raising the question of whether linezolid, given its adverse effects, is a potential option for long-term treatment or even suppression. In a study on chronic infections not limited to orthopedic infections, Vazquez et al (2016) concluded that with monitoring of adverse effects, a long-term treatment of greater than 6 weeks can be safely performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have analysed the factors associated with SAT failure. The failure rate seems higher among patients with a sinus tract and in those with infections caused by S. aureus [ 13 , 20 , 21 , 22 ].…”
Section: Evidence On Sat Efficacymentioning
confidence: 99%
“…Managing this situation, including the surgical and nonsurgical approaches, is complex. A curative approach is not possible for a small proportion of patients, whose only option for controlling symptoms and maintaining functionality is the indefinite administration of antibiotics, also know as suppressive antibiotic therapy (SAT), an apparently safe and well-tolerated treatment [ 3 , 4 , 5 , 6 ]. The antimicrobial impact of SAT is not limited to the infection site; one of the most concerning adverse effect is the disturbance of the commensal gut microbiota.…”
Section: Introductionmentioning
confidence: 99%